Aceh Tengah Racecourse - Rizqi Mardha Tillah (Universitas Syiah Kuala, 2019)
AbstractCentral Aceh Regency has many tourist attractions, one of which is horse racing, many tours from various regions of Aceh and Outside Aceh arrive. Horse racing that people often refer to as